Potential QT-prolonging drug-drug interactions in cardiovascular disease patients - Milena Kovačević; Milica Ćulafić; Marija Jovanović; Sandra Vezmar Kovačević; Katarina Vučićević; Branislava Miljković; Predrag Stevanović; Slavica Radovanović (Brazilian Journal of Pharmaceutical Sciences)
Abstract The study aimed to assess the prevalence and characteristics of potential drug-drug interactions (pDDIs) that increase the risk of QT prolongation, in a population of cardiovascular disease patients. An observational retrospective study was conducted at a cardiology ward. A total of 351 patients were included in the analysis, with almost equal gender distribution (female 48.4%) and mean age 70±10 years. In the total set of tested drug pairs (5620), QT-prolonging pDDIs were identified in 13 drug pairs on admission. The highest frequency was observed for ciprofloxacin (involved in 5 pDDIs), followed by propafenone (4 pDDIs) and beta2-agonists (4 pDDIs). The pharmacodynamic mechanism was involved in all pDDIs. The study revealed a low prevalence of QT-prolonging pDDIs on admission to the cardiology ward, about 3% in the studied population. However, given that underlying heart disease is a significant risk factor for the occurrence of QTc prolongation, the additional risk for acquired QT prolongation should not be neglected. Due to serious consequences caused by QT prolongation and TdP, the key role of health professionals is to identify predisposed patients and to recognize pDDIs involving QT-prolonging agents. Hence, patients’ modifiable risk factors for QT prolongation should be minimized, if not eliminated.